PENDALAMAN MATERI STANDAR ISI DAN STANDAR PROSES KURIKULUM PENDIDIKAN INDONESIA - Rudi Ilhami; Syahrani Syahrani (EDUCATIONAL JOURNAL : General and Specific Research, 2021)
Actually the content standard covers the minimum material scope and minimum competency level to achieve minimum graduate competence at certain levels and types of education. The curriculum is a set of educational plans and programs that are used as a reference by educational institutions that are adapted to the level and needs of students and by taking into account local culture. Policy on implementing the education unit level curriculum (KTSP), government decisions and regulations relating to the educational institution or level/type of school concerned. In the education process, curriculum management needs to be implemented so that curriculum planning, implementation, and evaluation run more effectively, efficiently, and optimally in empowering various learning resources, learning experiences, and curriculum components. (Sulfemi 2018: 4) Process standards are national education standards related to the implementation of learning in an educational unit to achieve graduate competency standards. The learning process in educational units is held interactively, inspiring, fun, challenging, motivating students to participate actively, and providing sufficient space for initiative, creativity, and independence in accordance with the talents, interests, and physical and psychological development of students.